2011
DOI: 10.1073/pnas.1009838108
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability of the fetal primate brain to moderate reduction in maternal global nutrient availability

Abstract: Moderate maternal nutrient restriction during pregnancy occurs in both developing and developed countries. In addition to poverty, maternal dieting, teenage pregnancy, and uterine vascular problems in older mothers are causes of decreased fetal nutrition. We evaluated the impact of global 30% maternal nutrient reduction (MNR) on early fetal baboon brain maturation. MNR induced major cerebral developmental disturbances without fetal growth restriction or marked maternal weight reduction. Mechanisms evaluated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
97
1
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 135 publications
(109 citation statements)
references
References 37 publications
6
97
1
5
Order By: Relevance
“…Similarly, the proper incorporation of new neurons and incoming afferents into the developing cortical sheet is thought to rely heavily on the subplate, a transient structure that becomes most prominent during the second trimester of primate pregnancy, and especially so under nascent associative cortices (23). Although speculative, the notion that SVZ and subplate processes might be particularly vulnerable to alterations of the prenatal environment capable of modifying BW has been lent support by a recently published study that provides experimental data on in utero adversity and brain development in primates (37). In this landmark study, modest maternal calorie restriction not only altered the balance between rates of cell birth and apoptosis in midgestation baboon SVZ but also reduced subplate neuronal network density.…”
Section: Modeling Prenatal Environmental Influences On Brain Developmentmentioning
confidence: 87%
See 1 more Smart Citation
“…Similarly, the proper incorporation of new neurons and incoming afferents into the developing cortical sheet is thought to rely heavily on the subplate, a transient structure that becomes most prominent during the second trimester of primate pregnancy, and especially so under nascent associative cortices (23). Although speculative, the notion that SVZ and subplate processes might be particularly vulnerable to alterations of the prenatal environment capable of modifying BW has been lent support by a recently published study that provides experimental data on in utero adversity and brain development in primates (37). In this landmark study, modest maternal calorie restriction not only altered the balance between rates of cell birth and apoptosis in midgestation baboon SVZ but also reduced subplate neuronal network density.…”
Section: Modeling Prenatal Environmental Influences On Brain Developmentmentioning
confidence: 87%
“…In keeping with this notion, most studies of the mechanisms underlying BW differences between MZ twins have focused on the placenta as the chief determinant of the in utero environment, linking withintwin differences in prenatal growth to inequitable access to placental tissue (35). The capacity of placental mechanisms for BW variation to also impact brain development has been established through experimental modification of effective placental transfer in animal models of placental insufficiency (1) and maternal undernutrition (36,37). In humans, ultrasonographic markers of placental insufficiency have been shown to predict neurobehavioral outcomes during fetal and early postnatal life (38,39).…”
Section: Modeling Prenatal Environmental Influences On Brain Developmentmentioning
confidence: 99%
“…Given that brain methylation cannot be studied in vivo in humans, and that epigenetic changes relevant for developmental programming can be part of a general response of the entire organism, 20,37 we used pyrosequencing to analyze rs6265 methylation in peripheral blood mononuclear cells (PBMCs) of 259 healthy humans. This site is differentially methylated in human PBMCs and, as predictable, methylation was affected by rs6265 genotype, given that only the Val allele has a CpG in this position (ANOVA: ND259; F 2,256 D1601.2; P < 0.001 ÃÃÃ ; ValVal > ValMet > MetMet; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…17 However, BDNF has not been associated with schizophrenia in recent large scale genome wide association studies. 18 BDNF expression is sensitive to early-life environment [19][20][21] and specifically hypoxic-stressors, 22,23 which, in turn, are critical factors involved in the pathophysiology of schizophrenia. [24][25][26][27] The failure to find association between BDNF and schizophrenia in large-scale case control studies may conceivably reflect a complex interaction of genotype and environmental experience that alters methylation status.…”
Section: Introductionmentioning
confidence: 99%
“…Intrauterine conditions that affect these structures and also are associated with increased risk for neuropsychiatric disorders include infection (9), maternal undernutrition (10,11), unhealthy maternal behaviors such as smoking or alcohol or drug use (12)(13)(14), and excessive maternal stress exposure (15). We and others have suggested that glucocorticoids (cortisol in humans) may play a salient role in this process (16)(17)(18).…”
mentioning
confidence: 99%